Aktualisasi Nilai-Nilai Kepemimpinan Astha Brata Untuk Mewujudukan Profil Pelajar Pancasila Melalui Sekolah Penggerak - Atik Dwi Kurniasih (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
To realize the Pancasila Student Profile, the Ministry of Education and Culture, Research and Technology issued one of the Independent Learning Program policies, namely the "Sekolah Penggerak". "Sekolah Penggerak" is implemented by strengthening the capacity roles of principals and driving teachers. The principal is a learning leader in each academic unit who is expected to move the school by collaborating with stakeholders to realize a student-centred school. "Guru Penggerak" are learning leaders who apply independent learning and move the entire educational ecosystem to realize learner-centred education. Becoming a learning leader as a "Sekolah Penggerak" Principal or "Guru Penggerak" requires a new paradigm shift. There is one Javanese local wisdom that can be actualized as a leadership model, namely Astha  Brata . This research is a descriptive study by examining the actualization of Astha  Brata 's leadership to realize the Pancasila Student Profile in the "Sekolah Penggerak". The method used is literature study through books, journals related documents and news/online. Study results show that Astha  Brata 's leadership values are still relevant and can be actualized to answer the challenges of being a school principal and "Guru Penggerak", who is expected to become a learning leader to realize the Pancasila Student Profile.